(untitled) (Altre Modernità, 2013)
During the 18th century British encyclopaedias included in their lemmata an increasing number of botanical lexis, that is the terminology pertaining to “that branch of natural history which treats of the uses, characters, classes, orders, genera, and species of plants. […] and what useful and ornamental purposes may be expected from the cultivation of it [i.e. botany]” (Encyclopaedia Britannica, 1768-1771, s.v. Botany). More often than not, these terms represented migrating plants coming from exotic places, new geographical areas, whether eastwards or westwards. The general aim of this survey is to investigate the representation of the botanical science in 18th-century universal and specialized encyclopaedias, starting from prefaces and going on with the micro-texts of the single entries s.v. Botany. The starting point is thus theoretical botany. A further point in the analysis focuses on applied botany and discusses those plants such as Camellia Sinensis, Coffea Arabica, Theobroma Cacao, Saccharum Officinarum and Cinchona Officinalis which were mostly exploited for commercial and/or medical reasons. The individual entries include the most tiny details on the single headwords-topics and also display an acceptable plurality of beliefs, viewpoints and perspectives, focussing on botanical descriptions, historical information, socio-cultural issues, legal, political and commercial considerations.